Finding the Copper Mine of the 21st Century:Conceptual Exploration Targeting for Hypothetical Copper Reserves - Sykes, John; Trench, Allan (Society of Economic Geologists, 2014)
An increasingly common perspective is that the predominant “copper mine of the 21st century” will be based on a large, low-grade deposit. Such a project will have to overcome “sustainable development” challenges and in turn may require higher copper prices than witnessed to date to achieve economic returns. Researchers therefore suggest that innovation and technological development in copper mining and processing are thus required to lower production costs. By contrast though, because much of the research assumes that new discoveries will be of lower quality than currently mined deposits, only a minimal role for copper exploration in the 21st centuryis anticipated, merely outlining further, ever lower quality copper resources. An alternate hypothesis is that the development problem is actually a discovery problem. The implication is that the exploration focus must change. Low-risk exploration during the recent copper price cycle has unveiled few new world-class copper deposits, thus the industry is largely now working with aged, suboptimal copper mine projects. As an illustration, sustainable development was only emerging as a concept when many of these projects were discovered, thus many are now proving problematic to advance toward mine status given current societal and environmental requirements. Exploration can help mitigate both resource depletion and sustainability problems, and the copper mine of 21st century may actually be a high-quality, but as yet undiscovered deposit, which can meet thetwin goals of economic and sustainable development.To discover high-quality sustainable and economic copper deposits, the exploration industry needs to build (or perhaps rebuild) its conceptual exploration capabilities. Three main conceptual challenges need to be addressed: (1) determining whether a copper deposit is likely to be economic from the earliest stages of exploration; (2) drawing sustainable development principles into the exploration targeting process; and (3) preparing for a future characterized by sudden, dramatic innovative technological changes that impact key elements of cost and uncertainty relating to the opening up of new exploration “search space” and other powerful external factors. To address these conceptual challenges and assist with exploration targeting, a number of new in-principle-only reserve types are introduced, including the following: (1) a “theoretical reserve” to aidunderstanding of the potential economics of a copper resource from the earliest stages of exploration; (2) a “conceptual reserve” incorporating sustainable development principles via the concept of “accessibility”; and (3) a “hypothetical reserve” representing undiscovered resources that have the potential to be both economic and accessible in the future.